Analisis Kemampuan Mahasiswa dalam Pembuatan Kalfis dengan GUI Matlab pada Materi Usaha dan Energi - Sri Endang Wahyuni; Fita Widiyatun; Puji Suharmanto (Navigation Physics : Journal of Physics Education, 2021)
Understanding of the material by students can be seen from the results of the work given. The purpose of this research was to examine, analyse and determine the abilities of student based on the result of the assignments given about making kalfis (physics calculator) for work and energy. The reseach method used is a qualitative method. The result showed that student could understand the material in making kalfis. This can be seen from the kalfis made by students that can be used properly.